100th anniversary of the scientific and theoretical journal «Teoriya i praktika fizicheskoy kultury»: present and future - Ponomarev, V.V.; Ukolov, A.V.; Efimov, A.A.; Isaev, R.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to systematise and identify scientific, practical, managerial, personnel, social and other aspects of the influence of the TiPFK journal on the formation and development of the physical culture and sports industry in the country and to design new guidelines, approaches and directions for the further development of the basic publication. Methods and structure of the study. A review and theoretical study was conducted throughout 2024. An analysis of the scientific and theoretical journal TiPFK was carried out for the last 20 years. The content and topics of scientific articles published by scientists and specialists in TiPFK were analysed. The main strategic directions of the journal’s activities and its influence on the formation and development of the physical culture and sports movement in the country were determined. Factual material was systematised, the activities of the journal as a whole were modelled, etc. Results and conclusions. Following the completion of a scientific and theoretical analysis of the formation and development of the TiPFK journal, a structural model was developed for the further progressive development of the country’s leading print sports publication. The model includes a strategy and directions for improving the magazine’s content in the coming decades, thereby supporting and expanding the scientific and methodological potential, traditions and practices of the physical culture, sports and health movement in Russia.